Change in sympathetic nerve firing pattern associated with dietary weight loss in the metabolic syndrome - Lambert, Elisabeth A.; Straznicky, Nora E.; Dawood, Tye; Sari, Carolina I.; Grima, Mariee; Esler, Murray D.; Schlaich, Markus P.; Lambert, Gavin W. (Frontiers in Physiology, 2011)
Sympathetic activation in subjects with the metabolic syndrome (MS) plays a role in the pathogenesis of cardiovascular disease development. Diet-induced weight loss decreases sympathetic outflow. However the mechanisms that account for sympathetic inhibition are not known. We sought to provide a detailed description of the sympathetic response to diet by analyzing the firing behavior of single-unit sympathetic nerve fibres. Fourteen subjects (57±2 years, 9 men, 5 females) fulfilling ATP III criteria for the MS underwent a 3-month low calorie diet. Metabolic profile, hemodynamic parameters and multi-unit and single unit muscle sympathetic nerve activity (MSNA, microneurography) were assessed prior to and at the end of the diet. Patients’ weight dropped from 96±4 to 88±3 kg (P<0.001). This was associated with a decrease in systolic and diastolic blood pressure (-12 ±3 and -5±2 mmHg, P<0.05), and in heart rate (-7±2 bpm, P<0.01) and an improvement in all metabolic parameters (fasting glucose: -0.302.1±0.118 mmol/l, total cholesterol: -0.564±0.164 mmol/l, triglycerides: -0.414±0.137 mmol/l, P<0.05). Multi-unit MSNA decreased from 68±4 to 59±5 bursts per 100 heartbeats (P<0.05). Single-unit MSNA indicated that the firing rate of individual vasoconstrictor fibres decreased from 59±10 to 32±4 spikes per 100 heart beats (P<0.05). The probability of firing decreased from 34±5 to 23±3 % of heartbeats (P<0.05), and the incidence of multiple firing decreased from 14±4 to 6±1 % of heartbeats (P<0.05). Cardiac and sympathetic baroreflex function were significantly improved (cardiac slope: 6.57±0.69 to 9.57±1.20 msec.mmHg-1; sympathetic slope: -3.86±0.34 to -5.05±0.47 bursts per 100 heartbeats.mmHg-1 P<0.05 for both). Hypocaloric diet decreased sympathetic activity and improved hemodynamic and metabolic parameters. The sympathoinhibition associated with weight loss involves marked changes, not only in the rate but also in the firing pattern of active vasoconstrictive fibres.